2016
DOI: 10.1002/fuce.201600079
|View full text |Cite
|
Sign up to set email alerts
|

Low Cost and Rapidly Processed Randomly Oriented Carbon/Carbon Composite Bipolar Plate for PEM Fuel Cell

Abstract: The objective of the present work is to develop carbon/carbon (C/C) composite bipolar plate at low cost with rapid processing time by a novel process. Carbon/carbon composite was developed using exfoliated carbon fiber reinforcement, isroaniso as primary matrix precursor, and resole type phenolic resin as secondary matrix precursor. Randomly oriented hybrid carbon fiber (T‐800 and P‐75) reinforced hybrid carbon matrix composite was fabricated. The slicing and channel forming were carried out using simple and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…In accordance with Verma et al, 2016, 33 the uniform distribution of fibers in the matrix in the x-y plane facilitates the interlocking mechanism between the filler and matrix entities, thus strengthening the composites and improving their dielectric properties.…”
Section: Resultssupporting
confidence: 81%
“…In accordance with Verma et al, 2016, 33 the uniform distribution of fibers in the matrix in the x-y plane facilitates the interlocking mechanism between the filler and matrix entities, thus strengthening the composites and improving their dielectric properties.…”
Section: Resultssupporting
confidence: 81%
“…They should fulfil many functions in a fuel cell stack such as feeding H 2 and O 2 gases through the flow field upon operation, heat transfer, physical separation of individual fuel cells in series, collection and transport of electrons from anode to cathode of adjacent cells (1,3). Significant efforts have resulted in light-weight and cost effective BPPs for fuel cell applications (2,(8)(9)(10)(11). In order to properly perform in a fuel cell, BPPs should provide mechanical, electrical, thermal and electrochemical stability of the system.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that as the molding temperature increased from 170°C to 200°C, the mechanical performance and electrical conductivity of the alloy decreased from 60 MPa to 10 MPa and from 425 S/cm to 300 S/cm, respectively, attributed to the changes in the resin network structure at high temperatures. [79][80][81][82][83][84] This phenomenon can be attributed to the thermal degradation and volatilization of diphenyl ether in the resin structure, leading to a significant decrease in the mechanical and electrical properties of the composite material. Minkook Kim proposed a flame treatment method for CBP and subjected CBP with phenolic resin as a binder to treatment at different temperatures.…”
Section: Polymersmentioning
confidence: 99%